Den engagerade reportern - Aare, Cecilia (Kriterium, 2024)
Social reportages are written by reporters who fight for the weak and expose injustices. So it is said in the profession, in handbooks and among the genre’s supporters. But what is hidden behind the ideal? And what does the commitment look like when it is converted into text? This book highlights reportages by some of the 20th century’s most celebrated Swedish reporters and examines the ways in which their texts convey a commitment to the reader. The narratologically based analyses are performed against a background of changing ideas about a reporter’s role in society. It turns out that the commitment is often time-related and can be counteracted by generalizing values about the depicted people. Here, the difference between empathy and compassion becomes crucial. The selected reporters represent Swedish social reportage at central turning points within the tradition. Ester Blenda Nordström and Gustaf Hellström have been chosen for the 1910s, Ivar Lo-Johansson for the years around 1930, Barbro Alving for the 1950s, Jan Guillou for the 1970s and Maciej Zaremba and Karen Söderberg for the 1990s and 2000s.